PROPOSALS FOR DEVELOPING GREEN SPACES IN THE SECOND UNIVERSITY POLE OF THE CITY OF TLEMCEN (ALGERIA) - Ikram Bendahmane (International Journal of Innovative Technologies in Social Science, 2024)
This work presents a critical appraisal of the organization of green spaces within the Second Pole of Tlemcen University, Algeria. The paper quantitatively and qualitatively analyzes the allocation of green spaces within the Second Pole, considering factors such as the recommended area per person (7 square meters) and the diversity of tree species (18). Furthermore, the paper identifies shortcomings in the current allocation of space for green areas and the limited selection of tree species within the Second Pole. Additionally, it critiques the ornamental trimming practices employed for various tree species. In response, the paper proposes specific policies for the organization of green spaces, advocating for both vertical and horizontal expansion of plant varieties.